Antiproliferative activity of methanolic extracts of genus Allium on human osteosarcoma SAOS-2 cells - Cheow, Pheik Sheen (2015)
Conventional treatments towards cancer bring along side effects to the patients. Plant extract treatments appear as new candidates for cancer treatment with fewer side effects. However, cytotoxicity effects of plant extracts on cancer are still lacking in scientific evidence. Allium plant extracts were hypothesed to able to inhibit growth of cancer cells. In this study, the cytotoxicity effects of two Allium plant extracts on Human osteosarcoma, Saos-2 cells were examined. Cell viability of Saos-2 cells was compared to the normal cells, Chang Liver Cells. Allium sativum fruit bodies and Allium ampeloprasum leaves were dried and blended into powder form. Then, they were extracted with methanol and evaporated to obtain crude extracts. Various concentrations of Allium extracts were used to treat the Human Saos-2 osteosarcoma cells. MTT assay was performed after 24, 48 and 72 hours of post treatment to evaluate the cytotoxicity effects. Allium sativum showed inducing of cell proliferation on Chang Liver Cells after 24h of treatment. In the other hand, it did not inhibit significant cell viability of Saos-2 cells for three different time slots. Allium ampeloprasum exhibit cytotoxicity towards both cell lines, but it kills more Chang Liver Cells than Saos-2 cells.